Modelling atomic layer deposition overcoating formation on a porous heterogeneous catalyst. Issue 34 (22nd August 2022) - Heikkinen, Niko; Lehtonen, Juha; Keskiväli, Laura; Yim, Jihong; Shetty, Shwetha; Ge, Yanling; Reinikainen, Matti; Putkonen, Matti
Abstract : Atomic layer deposition (ALD) was used to deposit a protective overcoating (Al2 O3 ) on an industrially relevant Co-based Fischer–Tropsch catalyst. Abstract : Atomic layer deposition (ALD) was used to deposit a protective overcoating (Al2 O3 ) on an industrially relevant Co-based Fischer–Tropsch catalyst. A trimethylaluminium/water (TMA/H2 O) ALD process was used to prepare ∼0.7–2.2 nm overcoatings on an incipient wetness impregnated Co–Pt/TiO2 catalyst. A diffusion–reaction differential equation model was used to predict precursor transport and the resulting deposited overcoating surface coverage inside a catalyst particle. The model was validated against transmission electron (TEM) and scanning electron (SEM) microscopy studies. The prepared model utilised catalyst physical properties and ALD process parameters to estimate achieved overcoating thickness for 20 and 30 deposition cycles (1.36 and 2.04 nm respectively). The TEM analysis supported these estimates, with 1.29 ± 0.16 and 2.15 ± 0.29 nm average layer thicknesses. In addition to layer thickness estimation, the model was used to predict overcoating penetration into the porous catalyst. The model estimated a penetration depth of ∼19 μm, and cross-sectional scanning electron microscopy supported the prediction with a deepest penetration of 15–18 μm. The model successfully estimated the deepest penetration, however, the microscopy study showed penetration depth fluctuation between 0–18 μm, having an average of 9.6 μm.